2015
DOI: 10.3329/ralf.v2i3.26169
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of canine Parvo virus infection in street dogs using rapid antigen detection Kit

Abstract: Canine parvovirus Street dog RapiGEN Ag. Test Kit Prevalence MymensinghCanine parvovirus is one of the most common infectious diseases of dogs. A study was carried out to diagnose the infection of canine parvovirus in street dogs from different places of Mymensingh Town. Rectal samples were collected from January to April, 2015. A total of 114 rectal swabs were collected conveniently from street dogs of Mymensingh. The samples were diagnosed using RapiGEN Canine Parvo Virus Ag Test Kit. The association of CPV … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 9 publications
0
4
0
Order By: Relevance
“…The diagnosis using PCR is highly recommended on faecal samples, in addition to histopathology and immunohistochemistry on necropsy specimens. However, in a poor resource setting, a rapid CPE antigen test kit may be employed especially in dogs showing evidence of diarrhoea (Nahat et al, 2015). Treatment for CPE is largely supportive and symptomatic.…”
Section: Introductionmentioning
confidence: 99%
“…The diagnosis using PCR is highly recommended on faecal samples, in addition to histopathology and immunohistochemistry on necropsy specimens. However, in a poor resource setting, a rapid CPE antigen test kit may be employed especially in dogs showing evidence of diarrhoea (Nahat et al, 2015). Treatment for CPE is largely supportive and symptomatic.…”
Section: Introductionmentioning
confidence: 99%
“…We did not observe significant relationships of sex, age, weight, and month of disease occurrence with CPV infection. Some reports indicate that males are at a higher risk of infection [3,[17][18][19]32], and yet another study reports that females are at a higher risk [17]. In some studies, it was observed that juvenile animals were at a higher risk, possibly due to lower levels of maternal antibody and lack of vaccination [2,3].…”
Section: Discussionmentioning
confidence: 99%
“…In Bangladesh, no molecular confirmation of the presence of CPV is available, although diagnosis with a rapid detection kit suggests endemic occurrence [17][18][19][20]. Pet practitioners regularly find CPV cases almost year-round and use a standard vaccination strategy for prevention.…”
Section: Introductionmentioning
confidence: 99%
“…The Protoparvovirus genus and Parvoviridae family emerged in the 1970s [ 4 , 5 ]. The virus spreads through the feces of affected dogs having high morbidity (100%), 10% mortality [ 6 ], and up to 90% fatality [ 2 ]. Dogs affected by CPV are usually characterized with fever, anorexia, lethargy, depression, vomiting, mucoid to hemorrhagic diarrhea, and sometimes leukopenia [ 18 ].…”
Section: Introductionmentioning
confidence: 99%